TINGKAT KELAYAKAN USAHA CABAI HIYUNG (Capsicumfrutescens) DI BEBERAPA LUAS LAHAN DI DESA HIYUNG KECAMATAN TAPIN TENGAN KABUPATEN TAPIN KALIMANTAN SELATAN - Mar'ati Fadillah; Ari Jumadi Kirnadi; Ana Zuraida (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2019)
Chili raw hiyung is the local flagship of Tapin Regency which is especially cultivated by farmers in Hiyung Village. The feasibility level is important in a business with the aim of obtaining a picture or clarity on a reasonable and more profitable land area. The study was conducted on 14 farmers with stratified random sampling and simple random sampling to determine the sample of each group. The results showed that the total cost of the average breeder Farmer I of Rp. 15,065,435, - and Farmer II amounting to Rp. 38,777,595, - with average production of Farmer I 1,078 kg and Farmer II of 2578 kg. average earnings of Farmer I amounted to Rp. 32,860,919, - and Farmer II amounting to Rp. 78,520,724, - farmer's average income of Rp. 25,119,484, - and Farmer II amounting to Rp.54.524.129, - and RCR average Farmers I of 2.15 and Farmer II of 2.04.